The Influence Of Urine Sample Type (Morning Urine And 12-Hour Urine) On Nitrates, Leukocytes, And Ph In The Carik Celup Method In Urine Of Patients With Urinary Tract Infection - Sholihah, Ica Pasi; Diarti, Maruni Wiwin; Urip, Urip; Resnhaleksmana, Ersandhi (Jurnal Analis Medika Biosains (JAMBS), 2024)
Urinalisa is a diagnostic test used to monitor kidney and urinary tract conditions. In the dipstick method, the most important parameters for urinalisa testing are bacteria, white blood cells, red blood cells, nitrite, and protein. Morning urine and urine collected 12 hours later can affect the testing results for nitrite, white blood cells, and pH in patients with urinary tract infections (UTIs). To determine the effect of urine sample type on the results of nitrite, white blood cells, and pH in patients with urinary tract infections (UTIs) using the dipstick method. This study employed an observational analytical design with a purposive sampling method, selecting patients with UTIs who visited RSUD Kab. Dompu in 2024 based on inclusion and exclusion criteria, resulting in a total sample size of 24. The results of the examination were mostly positive for nitrites and leukocytes, while the pH tended to be normal with morning urine samples. However, the majority were positive for nitrites and leukocytes, while the pH tended to be normal with 12-hour urine samples in UTI sufferers at District Hospital Dompu. There is an influence on examining the types of morning urine samples and 12 hour urine samples on the results of nitrite and leukocytes in UTI sufferers at District Hospital Dompu.